2017
DOI: 10.1089/aid.2016.0287
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: HIV Patient Systemic Mitochondrial Respiration Improves with Exercise

Abstract: In HIV-infected individuals, impaired mitochondrial function may contribute to cardiometabolic disease as well as to fatigue and frailty. Aerobic exercise improves total body energy reserves; however, its impact at the cellular level is unknown. We assessed alterations in cellular bioenergetics in peripheral blood mononuclear cells (PBMC) before and after a 12-week aerobic exercise study in sedentary HIV-infected subjects on stable antiretroviral therapy who successfully completed a 12-week aerobic exercise pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
2
13
1
Order By: Relevance
“…We also demonstrated that a recent bout of exercise did not alter PBMC mitochondrial function neither in high-fit nor in low-fit female individuals, indicating that a longer period of aerobic exercise training exposure might be required before the effects are reflected in metabolic PBMC profiles. This is in line with previous studies, which showed that 6 or 12 wk of aerobic exercise training increased mitochondrial function in respectively lymphocytes ( 36 ) and PBMCs ( 24 ) and found that protein and gene expression levels of mitochondrial markers in PBMCs were enhanced with 8 wk of aerobic exercise training ( 38 ), whereas a 2-wk aerobic exercise protocol did not alter mitochondrial function in PBMCs ( 37 ), indeed suggesting that longer-, but not shorter-term training status impacts PBMC mitochondrial function.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also demonstrated that a recent bout of exercise did not alter PBMC mitochondrial function neither in high-fit nor in low-fit female individuals, indicating that a longer period of aerobic exercise training exposure might be required before the effects are reflected in metabolic PBMC profiles. This is in line with previous studies, which showed that 6 or 12 wk of aerobic exercise training increased mitochondrial function in respectively lymphocytes ( 36 ) and PBMCs ( 24 ) and found that protein and gene expression levels of mitochondrial markers in PBMCs were enhanced with 8 wk of aerobic exercise training ( 38 ), whereas a 2-wk aerobic exercise protocol did not alter mitochondrial function in PBMCs ( 37 ), indeed suggesting that longer-, but not shorter-term training status impacts PBMC mitochondrial function.…”
Section: Discussionsupporting
confidence: 93%
“…To evaluate this potential in healthy individuals, we should better understand how longer-term lifestyle factors impact PBMC metabolism, and whether this is affected by a short-term lifestyle intervention. For example, previous studies have shown that PBMC metabolism not only responds to longer-term exercise training ( 24 ) but also to an acute exercise challenge ( 25 ). Since a single exercise bout often elicits a transient proinflammatory response whereas regular bouts of exercise induce an anti-inflammatory state ( 6 , 26 ), the impact of regular physical activity (long-term effect) and a single-exercise session (short-term effect) on PBMC metabolism could differ, yet this has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in support of this we have recently demonstrated that aging impairs mitochondrial respiratory capacity in human monocytes [57]. Exercise has been shown to increase mitochondrial respiration in peripheral blood mononuclear cells [58] and thus is a potential mechanism by which exercise alters monocyte function in older adults. To date, this is speculative and bears further investigation.…”
Section: Exercise and Monocyte Functionsupporting
confidence: 57%
“…Clinical studies show that PLWH undergoing an exercise regimen, had significant increases in VO 2 max and peripheral blood mononuclear cell mitochondrial respiratory capacity, spare respiratory capacity, and nonmitochondrial respiration (Kocher et al. ). We predict that similar improvements may be attained in PLWH with AUD, and this is the focus of current studies from our group.…”
Section: Discussionmentioning
confidence: 99%